Sejarah dan Ajaran Tarekat Syattariyah di Cirebon - Merita Dian Erina; Dila Alfiana Nur Haliza; Isna Fitri Choirun Nisa; Azizah Jumriani Nasrum; Wahyudin Darmalaksana (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the problems in history and teachings of the Syattariyah in Cirebon. The research method is used a qualitative method with a social intellectual history approach. The results of the study show that tarekat is one way to get closer to God. tarekat can also be referred to as an institution that houses people who will follow their path. One of the existing tarekat is Syattariyah. This began to appear in the 15th century in India. Then, it spread and expanded into Indonesia to the Java area. The name of this tarekat to Abdullah as-Syattar as its founder. The teaching is known to the Syattariyah congregation in Cirebon is the practice of remembrance of the seven dignities. From this research, it can be said that in the early 15th century the Syattariyah order and its well-known teachings were the remembrance of the seven dignities.